Propuesta de un plan de comunicación interna para la modalidad de estudios a distancia de la Universidad Nacional de Loja - Cumbicus Castillo, Perla Liliana (2016)
The development of this research work called “PROPUESTA DE UN PLAN DE COMUNICACIÓN INTERNA PARA LA MODALIDAD DE ESTUDIOS A DISTANCIA DE LA UNIVERSIDAD NACIONAL DE LOJA”. It was developed according to the rules of academic regime of the National University of Loja. The central problem of this project was: How improve the Internal Communication of the Distance Studies Method, of National University of Loja?; being this an institution with a large number of users and members; that It has an important role in the Lojana society and in the South of the country. The general objective is framed in: To determine the management of internal communication of Distance Studies Method, which will allow improve the institutional image The present investigation used several investigative methods; among them the deductive and inductive method in which the proposed topic is understood, the analytical method at the time of making the analysis of the bibliographical information as of the different tables and statistical graphs obtained from the result of the application of the instrument of collection of information such as the survey; the historical method was proposed to keep in mind the initial ideologies with which our alma mater was born. According to the results of the surveys conducted in the Modality of Distance Studies of the National University of Loja, it is known that a large majority use the website of the institution; while in a lower percentage they indicate that they receive academic information; while a minority considers that the information they receive from this institution is incomplete. From the conclusions obtained it is determined that the website of the institution is the most visited media by its public; the majority of the information consulted is academic; In addition it is concluded that the efficiency in the internal media is low. Finally, once the research process is concluded, we get to establish a proposal "PLAN DE COMUNICACIÓN INTERNA PARA LA MODALIDAD DE ESTUDIOS A DISTANCIA DE LA UNIVERSIDAD NACIONAL DE LOJA", which aims to strengthen the proper functioning of the internal communication of the MED; and that its publics are properly informed, resulting in a positive image of the same.